2019
DOI: 10.1016/j.kint.2018.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Lrig2 and Hpse2, mutated in urofacial syndrome, pattern nerves in the urinary bladder

Abstract: Mutations in leucine-rich-repeats and immunoglobulin-like-domains 2 (LRIG2) or in heparanase 2 (HPSE2) cause urofacial syndrome, a devastating autosomal recessive disease of functional bladder outlet obstruction. It has been speculated that urofacial syndrome has a neural basis, but it is unknown whether defects in urinary bladder innervation are present. We hypothesized that urofacial syndrome features a peripheral neuropathy of the bladder. Mice with homozygous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 52 publications
(92 reference statements)
6
65
0
Order By: Relevance
“…This could be investigated further by comparing the effects of direct activators of the NO‐cGMP signaling pathway on mutant and control mice. Consistent with the loss of EFS‐induced relaxation, however, Hpse2 mutant mice have fewer nerves in their outflow tracts and reduced Nos1 transcripts 12 . Therefore fewer nitrergic nerves may be the simplest explanation for impaired outflow relaxation upon nerve stimulation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This could be investigated further by comparing the effects of direct activators of the NO‐cGMP signaling pathway on mutant and control mice. Consistent with the loss of EFS‐induced relaxation, however, Hpse2 mutant mice have fewer nerves in their outflow tracts and reduced Nos1 transcripts 12 . Therefore fewer nitrergic nerves may be the simplest explanation for impaired outflow relaxation upon nerve stimulation.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that there is an overabundance of nerves in the bladder body of the Hpse2 mutant mouse 12 . Moreover, in children with UFS, the bladder has been described as hypercontractile 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, genes that have been associated with bladder malformations code for proteins implicated in the neuro‐muscular circuits required for bladder voiding . As examples, HPSE2 codes for heparanase 2 and LRIG2 codes for leucine rich repeats and immunoglobulin‐like domains 2, proteins detected in foetal bladder nerves; variants of these genes are implicated in urofacial syndrome …”
Section: Introductionmentioning
confidence: 99%
“…12,13 As examples, HPSE2 codes for heparanase 2 and LRIG2 codes for leucine rich repeats and immunoglobulin-like domains 2, proteins detected in foetal bladder nerves; variants of these genes are implicated in urofacial syndrome. 5,6,14 Also in the neuro-muscular category is CHRM3 that encodes M3, the key acetylcholine receptor expressed by detrusor smooth muscle cells that is required for parasympathetic-driven detrusor contraction and bladder emptying. 2,13,15 Weber et al 1 reported a family with six brothers who were born to consanguineous Turkish parents.…”
mentioning
confidence: 99%